Bioactivity of Aglaia spp. extracts on Callosobruchus maculatus Fabricius and Spodoptera litura Fabricius - Muning, Maznah (2014)
It has been proven that the Meliaceae family contains biologically active compounds and insecticidal properties. Some species in the Meliaceae family belong to the Aglaia genus which have potential compounds especially triterpenoid compounds to control insect pests. However, many Aglaia species have yet to be tested on important local pests. Hence, this study is carried out to ascertain potential compounds from the plant leaf extracts of two species of Aglaia, namely Aglaia odoratissima and Aglaia variisquama and to study the insecticidal activities of both species against Callosobruchus maculatus and Spodoptera litura. The plant leaf extracts were extracted using hexane, chloroform, ethyl acetate, and methanol. Mortality of C. maculatus showed significant difference (P<0.05) for solvent and concentration used in A. odoratissima and A. variisquama extract. Aglaia odoratissima extract of 10% methanol recorded 70±9.2% and 73±7.2% mortality after 24 hours and 48 hours of treatment respectively. Similar to A. odoratissima, 10% methanol of A. variisquama extracts showed highest mortality with 51±3.8% after 24 hours of treatment and 69±6.8% mortality recorded after 48 hours of the treatment. There were significant difference (P<0.05) recorded for concentration using for both species and 10% concentration was the most effective in reducing eggs laid by C. maculatus after treatments with only four to 14 eggs produced. Furthermore, total eggs produced and hatched also showed significant difference for concentration used with 10% concentration showed effectiveness of all solvent for both species. The tests recorded 50% reduction of eggs production and eggs hatched compared to their control. Repellency activity showed significant different for duration (hour) of C.maculatus exposed to treatment with 50% of repellency was recorded after five hour of treatment for both species. Bioassay against S.litura showed A. variisquama recorded high mortality in preliminary tests with 50.00±5.1 mortality. After further studies were done, concentration used showed significant difference (P<0.05) for mortality, growth inhibitory and antifeedant test against S. litura larval. Toxicity test showed all solvents were effective against S. litura larva at 1% concentration with highest mortality being recorded for chloroform solvent with 48±2.3% mortality. Growth inhibitory bioassay also shows effectiveness for all solvents at 1% concentration especially methanol solvent with almost 50% reduction in larval weight compared to its control. Extract of 1% of hexane, chloroform and methanol were found to be effective with over 20% different of leaves weight consumed recorded compared to their control. Gas chromatograph mass spectrum analysis on A. odoratissima and A. variisquama had shown both species contained highly with terpens especially sesquiterpenoid and triterpenoid group. Both groups have been studied and some of the compounds in both groups have promising bioactivity against insect especially triterpenoid. Result against C. maculatus and S. litura can be concluded that A.odoratissima and A. variisquama have potential as botanical insecticide and showed high amounts of potential sesquiterpenoid and triterpenoid.